Development of hard and optically transparent Al‐Si‐N nanocomposite coatings. (10th February 2016) - Mishra, S.K.; Kumari, Swati; Soni,
Abstract : Nanocomposite Al‐Si‐N coatings have been successfully deposited by d.c. magnetron sputtering on different technological important substrates such as Si, SS‐304, and glass. In this manuscript, the structural, mechanical, and optical properties of the Al‐Si‐N have been investigated. A solid solution of Al‐Si‐N phase is formed with a wurtzite hexagonal nc ‐AlN structure. The Al‐Si‐N films showed a high hardness 30 GPa, modulus 300 GPa, and elastic recovery, We = 54% and H/E = 0.1, which are the essential conditions for enhanced crack‐resistant coatings. Moreover, the films were optically transparent in ultraviolet and visible range with a transparency of 90% with an optical band gap of 3.8 eV. Copyright © 2016 John Wiley & Sons, Ltd.